Dinamika kepemimpinan dalam organisasi modern - Fithriyah, Lailatul (Maliki Interdisciplinary Journal, 2026)
Leadership is one of the most crucial aspects in determining the direction, development, and success of an organization. Leaders are not only responsible for giving instructions, but also for acting as inspirators, communicators, and driving forces in organizational change processes. This article comprehensively examines leadership dynamics, including human relations in leadership, variations of leadership styles, and the role of leaders as agents of change. The analysis is based on the work of (Tampubolon, 2022) and is strengthened by cross-generational leadership theories that emphasize behavioral aspects, human relations, and leadership effectiveness (Fiedler, 1967; Thoha, 2006). To enrich the ethical dimension of modern leadership, this study integrates the prophetic leadership model as a form of spiritual leadership that emphasizes moral values, integrity, and social responsibility in leadership practices (Fathih et al., 2024). The findings indicate that leadership dynamics are not merely a matter of style and position, but rather reflect a leader’s ability to understand people, interpret situations, and navigate change effectively. Through adaptive, participatory, and communicative leadership grounded in ethical values, organizations can achieve long-term sustainability.